2015
DOI: 10.1111/jcpt.12323
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin serum trough concentration vs. clinical outcome in patients with gram-positive infection: a retrospective analysis

Abstract: This retrospective analysis failed to demonstrate an association between vancomycin trough concentration and the clinical and microbiological response. Prospective controlled studies are necessary to further establish the need for the higher trough concentrations normally cited for clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Consistent with their finding, 71·4% (130/182) of our paediatric patients experienced treatment success with vancomycin. In our study, the incidence of nephrotoxicity was 2·4% (4/165) in children receiving at least 72 h of vancomycin therapy, which is lower than previously reported . Using a similar definition for nephrotoxicity, McKamy et al .…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Consistent with their finding, 71·4% (130/182) of our paediatric patients experienced treatment success with vancomycin. In our study, the incidence of nephrotoxicity was 2·4% (4/165) in children receiving at least 72 h of vancomycin therapy, which is lower than previously reported . Using a similar definition for nephrotoxicity, McKamy et al .…”
Section: Discussioncontrasting
confidence: 53%
“…found that higher vancomycin trough levels did not result in an improved clinical response but likely increased the incidence of nephrotoxicity. A recent study of Chinese adults with Gram‐positive infection did not find any association between the vancomycin trough concentration and the clinical and microbiological responses . In addition, several meta‐analyses have shown that higher vancomycin trough levels (15 mg/L or greater) were not associated with significantly reduced treatment failure, persistent bacteraemia or mortality .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations